INTERNATIONAL TRANSPORT LOGISTICS - S. I. Lashko (Научный вестник Южного института менеджмента, 2016)
In article the international transport logistics which predicts the serious and big future is analyzed. The predominating concept of «intermodalnost» of transportations is noted.